The MOORA method for selecting software App: price-quality ratio approach - Akmaludin, Akmaludin; Sihombing , Erene Gernaria; Dewi, Linda Sari; Rinawati , Rinawati; Arisawati , Ester (Politeknik Ganesha Medan, 2021)
Seeing the rapid progress of software app. in today's destructive era, the need for software app. is very reliable for industrial progress in the era of the 4.0 generation. Especially in object-oriented software app. The main objective of this research is to measure the technical capabilities of object-based software app. and to find out the process of selecting the best number of app.software in terms of the appropriate price. Many techniques can be developed in object-based software app. such as class implementation, Inheritance, Encapsulation, Polymorphic, Constructor, Accessor, Mutator, Visibility, Overwrite and Overload. This technique is an advantage of object-based software app. Taking advantage of these advantages causes difficulty in selecting and evaluating software. Indeed, it is very difficult to evaluate software products, because they are qualitative. In order for the assessment to be objective, it requires good method collaboration, thus an objective method is needed in the assessment of the selection of a number of program app. The test was carried out with the Multi Objective Optimization by Ratio Analysis (MOORA) method collaborated with the Price-Quality Ration approach. The results obtained are the selection of object-based software app. that can be done optimally and provide efficiency in the benefits and costs incurred.